Remarks on the South American Iguanid Lizard Liolaemus anomalus Koslowsky, and the Synonymy of Phrynosaura werneri Müller (Reptilia, Lacertilia, Iguanidae) - Cei, José Miguel Alfredo María (1979)
A description of the neotype of Liolaemus anomalus Koslowsky is given, with comments about its relationships, geographical variation and ecology. The comparison of new samples of this poorly known tropidurine lizard with the holotype of Phrynosaura werneri Müller suggests their synonymy.